The Effect Of Giving Educative Videos About Diabetic Foot Gymnastics On The Implementation Of Foot Exercises In Patients With Type 2 Diabetes Mellitus At Chania Care Center Kediri District - Juwariyah, Titik; Winarni, Jajuk; Lailaturohmah, Lailaturohmah; Mildawati, Ratna (Innovative: Journal Of Social Science Research, 2021)
Diabetes mellitus is a chronic disease that requires long-term treatment. In diabetes mellitus patients, physical exercise is often neglected, one of which is due to lack of knowledge. This research aims to determine the effect of educational videos about diabetic foot exercises on implementing foot exercises in type 2 diabetes mellitus patients at the Chania Care Center, Kediri Regency. The research design used a quasi-experimental design with a one-group pretest-posttest approach. The population in this study was 30 respondents. A total sample of 30 respondents was taken using the total sampling technique. The instrument used the observation sheet. Nominal data scale. The analysis test uses the Mc Nemar test. In this research, before giving the educational video, almost all of them did not do leg exercises, namely 23 respondents (76.7%), after giving the educational video, almost all of them did foot exercises, 26 respondents (86.7%). The results of the Mc Nemar Test analysis showed an effect of providing educational videos about diabetic foot exercises on implementing foot exercises in type 2 diabetes mellitus patients at the Chania care center in Kediri district (p-value = 0.001 < α=0.05). A person's knowledge can increase after being given education or health education. Educational methods with videos about diabetes foot exercises can increase DM patients' knowledge of doing foot exercises to improve peripheral blood circulation to the feet.